Barriers to Implementing Climate Policies in Agriculture: A Case Study From Viet Nam - Giles, James; Grosjean, Godefroy; Le Coq, Jean-Francois; Huber, Bernhard; Bui, Vinh Le; Läderach, Peter (Frontiers in Sustainable Food Systems, 2021)
Abstract Agriculture is both highly sensitive to climate change and a major global emitter of greenhouse gasses (GHG) emissions. With growing international pressure to curb global emissions through the 2015 Paris Agreement and mounting climate change-related losses in agriculture, countries are requiring an increasingly robust agricultural policy framework. This paper takes an in-depth look at the agricultural sector in Viet Nam, contributing to a better understanding of the main bottlenecks in implementing the Paris Agreement. Evaluating the relevance and impact of selected barriers for the implementation of current climate policies and their implications for Nationally Determined Contribution (NDC) design. To address these questions, an exploratory mixed method approach was employed; i) identifying and mapping key policies, ii) reviewing global literature sources on barriers, iii) conducting stakeholder interviews (n=25) and iv) follow-up quantitative surveys (n=16). The interviews revealed numerous barriers within Viet Nam’s institutional setting that acted to impede the creation and implementation of climate policy. Insufficient inter-ministry collaboration and information sharing restricted the overall success of climate policy, with poor representation of non-lead ministries in drafting and inadequate channels for bottom up engagement also considered major constraints. These coupled with gaps in financing make for fragmented policies that often lack clear implementation guidelines, particularly at a local level. The NDC process presents an opportunity for Viet Nam to coordinate their cross sector climate response around a single international agreement, facilitating greater inter-Ministry information and data sharing, while utilising the technical and financial support provided through international partners to build capacity in this vital area.